Hubungan Karakteristik Ibu Dengan Tingkat Pengetahuan Tentang Menopause Di Desa Giri Sasak Kuripan Selatan Kabupaten Lombok Barat - Maryam, Siti; Pratiwi, Dita Retno (Universitas Qamarul Huda Badaruddin, 2020)
Pre menopause is a problem for women which can be caused by a lack of knowledge about menopause, which causes mothers to feel anxious about menopause. Objective: to determine the relationship between maternal characteristics and the level of knowledge about menopause in Giri Sasak Kuripan Selatan Village, West Lombok Regency. This study used a descriptive correlational analytic design with a cross sectional approach. Population of women aged 35-59 years in Giri Sasak Kuripan Selatan Village, West Lombok Regency. The sampling technique uses total sampling with a sample of 69 people. Data collection using a questionnaire. The study was conducted on 2019. Data analysis using Kendall Tau. the characteristics of respondents most respondents aged an average of 35-45 years (69.6%), worked (62.3%), had a high school / vocational high school education (58.0%), a moderate level of knowledge (52.2%). Kendall Tau correlation test results age with the level of knowledge about menopause obtained a CC value of 0.257 (low) with a p value of 0.026, education with a level of knowledge about menopause obtained a CC value of 0.589 (moderate) with a p value of 0.000 and work with the level of knowledge about menopause obtained a CC value of 0.493 (moderate) with a p value of 0.000. There is a relationship between age, education, mother's occupation with the level of knowledge about menopause in Giri Sasak Kuripan Selatan Village, West Lombok Regency.